Autonomous Assistance Control based on Inattention of the Driver when Driving a Truck Tract. - Bunces Naranjo, Elvis Andrés (2018)
This article proposes the autonomous assistance of a Truck based on a user's inattention analysis. The level of user inattention is associated with a standalone controller of driving of assistance and path correction. The assis-tance algorithm is based on the kinematic model of the Truck and the level of user inattention In addition, a 3D simulator is developed in a virtual environ-ment that allows to emulate the behavior of the vehicle and user in different weather conditions and paths. The experimental results using the virtual simula-tor, show the correct performance of the algorithm of assistance proposed.